COCUKLARDA İNFEKSİYONA SEKONDER PLEVRAL EFFÜZYONLARA YAKLAŞIM: 6 YILLIK DENEYİM - CERRAH CELAYİR, Ayşenur and İNALHAN, Meral and ETKER, Şeref and İNAN, Savaş (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Between 1993 and 1999, 47 patients with pleural effusions were treated by medical therapy and chest tube drainage in Paediatric Department of Zeynep Kamil Hospital. These cases were reviewed. Results.- The initial presentations in these cases were as follows: Empyema thoracis 20, parapneumonic effusion 20, tuberculous effusion 7. Only one patient with tuberculous effusion had required decortication. The mean hospitalization duration was 14.4 ± 6.2 days. Conclusion.- In our experience, most of the children with pleural effusions and empyemas can be treated by an effective medical treatment or by simple chest tube drainage. However, a few patients with persistent fever and respiratory distress may need further surgical interventions.